Domestic versus cross-border mergers and acquisitions: An investigation of the operating performance of acquiring firms from BRICS countries - Tran, Linh Thanh (2015)
This work attempts to contribute to overall research on mergers and acquisitions (M&As) as well as the nascent literature on cross-border M&As initiated by emerging market bidders. We assess and compare impacts of domestic and cross-border M&As upon long-run operating performance of acquiring firms from BRICS (Brazil, Russia, India, China, South Africa) and analyse the explanatory role of deal characteristics using a sample of 101 domestic and 49 cross-border M&As from January 1, 2006 to December 31, 2011. By employing three models including change, intercept and extended regression models and four operating performance indicators comprising operating cash flow return, return on assets, inventory turnover and sales growth, we obtain the following results. Regarding domestic bids, a change model reveals a significant decline in bidders’ median operating performance from the pre- to post-acquisition years; whereas an intercept model notes significantly positive acquisition-induced changes in operating performance. Concerning cross-border M&As, operating impacts are not consistent across performance measures within each model but in general foreign takeovers result in significantly negative or statistically insignificant performance changes. Cross-border M&As overall induce more negative changes in operating performance than domestic takeovers. However, after controlling for persistence in performance and effects of deal-specific factors, foreign deals significantly improve sales growth more than domestic transactions. Finally, we find that while industrial relatedness between acquiring and target firms is not capable of explaining post-M&A performance, relative size in an acquisition and payment method can predict some of the observed changes in firm performance.